2018
DOI: 10.7704/kjhugr.2018.18.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DA-9701 on Feeding Inhibition Induced by Acute Restraint Stress in Rats

Abstract: Background/Aims: Stress has a role in the pathogenesis of functional dyspepsia (FD) and influences food intake in humans and animals. Prokinetic drugs have been used in FD, and some of these drugs reverse the feeding inhibition (FI) induced by acute restraint stress in rats. We aimed to evaluate the effect of DA-9701 on FI induced by acute restraint in rats. Materials and Methods: Male Sprague-Dawley rats were divided into 6 groups: Control (no stress), Stress+vehicle, and Stress+DA-9701 at doses of 1, 3, 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In DA-9701-treated dogs, meal-induced gastric volumes significantly increased and persisted, a finding comparable to that achieved with sumatriptan [69]. DA-9701 may be effective in restoring restraint stress-induced food intake inhibition in rats, and this effect appears to be related to enhanced gastric accommodation by 5-HT 1A agonism [70]. Further, THB isolated from DA-9701 alleviated impaired gastric compliance in the rat after stress induction and relaxed the proximal stomach via 5-TH 1A agonism [71].…”
Section: Da-9701mentioning
confidence: 88%
“…In DA-9701-treated dogs, meal-induced gastric volumes significantly increased and persisted, a finding comparable to that achieved with sumatriptan [69]. DA-9701 may be effective in restoring restraint stress-induced food intake inhibition in rats, and this effect appears to be related to enhanced gastric accommodation by 5-HT 1A agonism [70]. Further, THB isolated from DA-9701 alleviated impaired gastric compliance in the rat after stress induction and relaxed the proximal stomach via 5-TH 1A agonism [71].…”
Section: Da-9701mentioning
confidence: 88%
“…Another study with Beagle dog showed that oral administration of DA-9701 induced gastric accommodation dose-dependently during the postprandial phase similar to the oral administration of sumatriptan (126). Restraint stress-induced feeding inhibition was reversed by oral DA-9701, and this effect was blocked by a 5-HT 1A antagonist in a rat study (127). A tissue bath study using rat gastric muscle strip suggested that the nitrergic rather than the purinergic pathway was involved in gastric accommodation by DA-9701 (128).…”
Section: Effects On Gastric Accommodationmentioning
confidence: 90%
“…1). 5 Based on the experience of the previous experiment, we thought it would be possible to measure GE with 3D micro-CT in rat without sacrifice.…”
Section: To the Editormentioning
confidence: 99%